2019
DOI: 10.1097/tme.0000000000000256
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Care of Individuals With Sickle Cell Disease in the Emergency Department Using a Quality Improvement Framework

Abstract: Sickle cell disease (SCD) is a severe chronic disease that leads to premature mortality caused by serious complications of the disease such as acute chest syndrome, stroke, and sepsis. Patients presenting to the emergency department (ED) with pain due to vaso-occlusive crisis (VOC) are at a higher risk for complications, making it imperative that emergency nurses, nurse practitioners, and physicians are knowledgeable about SCD and understand the other associated complications besides VOC. Because of the comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
0
2
1
Order By: Relevance
“…8,10 Most studies also noted that SCD pain is the most dominant feature of ED presentation. 20,36 However, our study found that higher pain frequency was a significant predictor of having delayed ED care. Possible reasons for this can be considered in light of our other findings.…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…8,10 Most studies also noted that SCD pain is the most dominant feature of ED presentation. 20,36 However, our study found that higher pain frequency was a significant predictor of having delayed ED care. Possible reasons for this can be considered in light of our other findings.…”
Section: Discussioncontrasting
confidence: 56%
“…Other guidelines for SCD care in the ED exist. 1 , 20 , 43 From a policy and educational perspective, however, more work is needed to reduce these “educational gaps and biases among providers, staff, and patients [that] create barriers to communication and trust, and erode the provider-patient relationship.” 43 Building patient and ED provider communication will be fundamental to improving care for the SCD patient population in the United States, with the goal of improving quality of life and ultimately reducing morbidity and mortality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation